IMPLEMENTASI EKSTRAKURIKULER KEPRAMUKAAN BERBASIS KARAKTER DALAM PENGUATAN MATERI PENDIDIKAN AGAMA ISLAM DI MA NEGERI 3 KEDIRI - Devi Risalatul; Imron Arifin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2020)
Education is a process of guidance that is carried out consciously, knowledge, and values ​​in students towards the formation of the main personality. It is not only the transformation of knowledge that is carried out but rather the formation of a strong personality. An intelligent nation is indeed needed in building a nation and a state, but intelligence alone is not enough if it is not balanced with a good and strong character. This study aims to describe and analyze the extracurricular values ​​of character-based scouting in strengthening Islamic education material at MA Negeri 3 Kediri. For this reason, researchers are interested in conducting research on scouting extracurricular activities. There are 3 focuses in this research, namely: 1) How is the implementation of character-based scouting extracurricular activities in strengthening Islamic education material in MAN 3 Kediri? 2) What are the extracurricular values ​​of character-based scouting in strengthening Islamic religious education material in MAN 3 Kediri? 3) What are the impacts of the implementation of character-based scouting extracurricular activities in strengthening Islamic religious education materials in MAN 3 Kediri? This research is a descriptive study with a qualitative approach to data collection techniques using observation, interviews, and documentation. While the data analysis technique uses domain analysis techniques with steps of data reduction, data display, and verification. The data validity test was carried out through a credibility test, transferability test, dependability test, and confirmability test. The results of the research show that from the implementation of scouting extracurricular activities, there is an education in scout extracurricular activities which have the main character values, namely religious, nationalist, independent, mutual cooperation, and integrity in accordance with Islamic religious education material.